Spectrophotometric analysis of crown discoloration induced by two different sealers: An In vitro study - Rashmi Keshav Chahande; Sanjay S Patil; Vandana Gade; Rishikesh Meshram; Deepika J Chandhok; Deepa A Thakur (Indian Journal of Dental Research, 2017)
Context: Endodontic materials have been assessed with regards to their potential for dental staining. Aims: To evaluate the coronal discoloration effect of Apexit Plus and Resino Seal in mandibular premolars using spectrophotometer. Settings and Design: The study design was original research. Materials and Methods: Forty human single-rooted mandibular first premolar teeth were selected for the study. They were divided into four groups of ten specimens each. Group 1 - Apexit Plus sealer, Group 2 - Resino Seal sealer, Group 3 - positive control (Blood), and Group 4 - negative control (distilled water). Teeth were resected 3 mm below at cementoenamel junction. In all samples, access cavities were prepared, instrumented, and irrigated. Sealers were mixed and placed into the pulp chamber through cervical access and control groups were filled with blood and distilled water. Coronal orifices were sealed using self-cure glass ionomer cement. Samples were analyzed using spectrophotometer to determine the discoloration in each group at 10, 17, and 24 days interval. Statistical Analysis Used: Statistical analysis used Wilcoxon signed-rank test. Results: All sealers used in the present study caused a progressive coronal discoloration over a time period of 17–24 days. There was statistically significant difference between resino seal sealer and apexit plus sealer , with resino seal showing greater coronal discoloration. Conclusion: Resino seal sealer has greater potential to cause discoloration of crown as compared to apexit plus sealer over a period of time.